Skeletal muscle monocarboxylate transporter content is not different between black and white runners - Harley, Y. X. R.; Kohn, T. A.; St. Clair Gibson, A.; Noakes, T. D.; Collins, M. (European Journal of Applied Physiology, 2009)
The superior performance of black African runners has been associated with lower plasma lactate concentrations at sub-maximal intensities compared to white runners. The aim was to investigate the monocarboxylate transporters 1 (MCT1) and MCT4 content in skeletal muscle of black and white runners. Although black runners exhibited lower plasma lactate concentrations after maximum exercise (8.8 ± 2.0 vs. 12.3 ± 2.7 mmol/l, P < 0.05) and a tendency to be lower at 16 km/h (2.4 ± 0.7 vs. 3.8 ± 2.4 mmol/l, P = 0.07) than the white runners, there were no differences in MCT1 or MCT4 levels between the two groups. For black and white runners together, MCT4 content correlated significantly with 10 km personal best time (r = -0.74, P < 0.01) and peak treadmill speed (r = 0.88, P < 0.001), but MCT1 content did not. Although whole homogenate MCT content was not different between the groups, more research is required to explain the lower plasma lactate concentrations in black runners.